2018
DOI: 10.3390/agronomy8120287
|View full text |Cite
|
Sign up to set email alerts
|

Response of Yellow Quality Protein Maize Inbred Lines to Drought stress at Seedling Stage

Abstract: This study seeks to evaluate the response of 17 yellow Quality Protein Maize (QPM) inbred line seedlings to drought stress (DS), using different morphophysiological traits (plant height (PH), chlorophyll content (CC), stem diameter (SD), proline content (Pro), photochemical efficiency of photosystem II (PS II), canopy temperature (CT) and substomatal carbon dioxide concentration (Ci). The experiment was laid out in a randomized complete block design (RCBD) and replicated three times in a growth chamber. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(29 reference statements)
2
2
1
Order By: Relevance
“…Contrary to what was reported by Chiuta and Mutengwa [76] in maize, no significant variation of Chla or b content was observed under water-deficit conditions. However, a significant decrease in the Chla/Chlb ratio was observed in both populations and a significant increase in carotenoids content in 'Fandango'.…”
Section: Diversity Of Responses Under Moderate Stress Similar Stratecontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to what was reported by Chiuta and Mutengwa [76] in maize, no significant variation of Chla or b content was observed under water-deficit conditions. However, a significant decrease in the Chla/Chlb ratio was observed in both populations and a significant increase in carotenoids content in 'Fandango'.…”
Section: Diversity Of Responses Under Moderate Stress Similar Stratecontrasting
confidence: 99%
“…Growth is the trait in plants that is most sensitive to water deficit, with decreases in growth preceding decreases in photosynthesis [74]. Indeed, in our field study, and in agreement with previous results in maize populations [75][76][77] plant stem height (PH) was already affected by water deprivation in all the four populations at a moderate water deficit (20% SWC), while for the majority of the populations, leaf gas exchange parameters of the stress exposed plants were similar to that of the non-stressed plants until 87% of the soil moisture was depleted (13% SWC). A reduction on shoot length (SL) when water deficit was still moderate (25-15% SWC) was also observed for maize seedlings grown under the growth chamber conditions experiment agreeing with previous results from Reference [67].…”
Section: Diversity Of Responses Under Moderate Stress Similar Stratesupporting
confidence: 92%
See 1 more Smart Citation
“…It has been reported that the spectral reflectance on the leaf was higher for maize [25], snap beans [24], and green peas [16] under drought stress than under optimal water supply conditions. Others [35] recorded lower chlorophyll content (SPAD unit) for most inbred maize lines under drought stress condition than in the well-watered plants. On the contrary to these statements the results in this study were different; the leaf and canopy spectral reflectance of sweet corn hybrids measured under low rain-fed (I 0 ) condition were lower than under optimal water supply condition (Table 1).…”
Section: Discussionmentioning
confidence: 96%
“…As a multidimensional stress, water limitation triggers a wide variety of plant responses; these range from responses at the physiological and biochemical levels to the molecular level [12][13][14][15][16]. When external drought stimuli are perceived and captured by sensors on cell membranes, the signals are transmitted through multiple signal transduction pathways.…”
Section: Introductionmentioning
confidence: 99%